Incidence, patterns and prognosis of first distant recurrence after surgically treated early stage endometrial cancer: Results from the multicentre FRANCOGYN study group. Issue 4 (April 2019) - Ouldamer, Lobna; Bendifallah, Sofiane; Body, Gilles; Touboul, Cyril; Graesslin, Olivier; Raimond, Emilie; Collinet, Pierre; Coutant, Charles; Bricou, Alexandre; Lavoué, Vincent; Lévêque, Jean; Daraï, Emile; et al.
Abstract: Patterns of distant metastatic failure of endometrial cancer (EC) by specific anatomic site are not well described in the literature. In this manuscript, we evaluated the metastatic patterns of EC cancer and analysed the potential distribution of metastatic disease in this malignancy. Methods: A total of 1444 women with EC were identified. Of which we extracted women with locoregional and distant recurrence or with distant recurrence alone. Women were scored based on first site of metastasis: multiple versus one site: bone, brain, lung, liver or sus diaphragmatic lymph nodes. Results: 110 women developed distant metastatic disease with (n = 37(33.6%)) or without (n = 73(66.4%)) locoregional recurrence, including 39 women with exclusive first site of metastatic disease and 34 women with multiple sites of metastatic disease. When considering all women, the most common exclusive first site of metastasis was lung (42.8%). The median time to develop distant metastases was shorter after the completion of treatment for exclusive brain metastatic disease compared with other sites of metastatic− disease (7 months vs, 9 for lung, 10 for liver, 19 for bone and 27 months for sus-diaphragmatic LN; P  = 0.004). The rate of 3-year overall survival was higher in the sus-diaphragmatic LN metastase group (83.3% vs 50.6% for lung, 37.3% for bone, 16.7% for brain and 0% for liver; P  = 0.0059). Conclusion: The present study has demonstrated the site-specific patterns of metastases. These data support current clinical practice of screening for site-specific metastatic disease after initial treatment of early stage EC based on concerning women-specific signs or symptoms.